Effusive pericarditis in the pathogenesis of cardiac arrhythmias in COVID-19: a case series - Z. N. Sukmarova; M. A. Saidova; Yu. V. Ovchinnicov (Кардиоваскулярная терапия и профилактика, 2022)
A wide variety of non-pulmonary manifestations of a coronavirus disease 2019 (COVID-19) has enriched clinical performance of cardiac diseases with atypical symptoms. Two COVID-19 cases are presented, where sinus bradycardia and syncope, which are rare in COVID-19, were the leading ones after the infection. The patients had no prior cardiovascular diseases, while the examination did not detected neurological pathology and myocarditis. Echocardiography showed relatively small pericardial effusion, which is supposed to be a cause of the symptoms as the diagnosis to exclude. A local buildup of inflammatory fluid around the sinus node and extensive ganglion plexuses around the atria can possibly affect the automatism and chronotropic compensation in addition to the myocardial inflammation. As part of the treatment against the hydropericardium syndrome, the symptoms disappeared, without reoccurring within subsequent 6-month follow-up. The third clinical case regards the pandemic outbreak, when we could not even suspect that the systemic inflammation would persist for many months after COVID-19 and radiofrequency ablation can lead to sudden cardiac death.